Opal-templated films for optical strain sensing - Nonthanan Sitpathom (2020)
© 2020 Optical Society of America under the terms of the OSA Open Access Publishing Agreement A polydimethylsiloxane film patterned by a self-assembled array has been demonstrated as a strain sensor. A monolayer of 580 nm polystyrene spheres prepared by convective deposition was the template to transfer a periodic pattern to a polydimethylsiloxane (PDMS) film. Optical diffraction through the stretched PDMS film, enabled strain sensing perpendicular and parallel to the stretching direction, with sensitivities of 1.7 nm/% strain and 4.0 nm/% strain, respectively. The PDMS film was used as a vibration sensor at 50 Hz.